Sustainable Competitive Advantage of Strategic Corporate Social Responsibility in Thai Companies - Chutkaew, Chutchanok (2007)
Today, there is a high competition in economic market. CSR is viewed as the strategy which leads companies not only to gain competitive advantage beyond competitors in terms of cost leadership and differentiation but also strengthen brand awareness and corporate reputation. Therefore, most Thai companies interest to engage in CSR and integrate it into corporate vision and mission in order to achieve the maximization of both economic profits and non financial performance. This dissertation explores the factor of sustainable competitive advantage of strategic corporate social responsibility (CSR) in Thai Companies. In this regards, the areas of this study cover to CSR types, the motivations and drivers, strategic CSR activities and benefits and perception of CSR in Thailand. The findings will be analyzed by compare and contrast across industry and business size. The findings are possibly benefits to Thais management in terms of understand the relation of CSR concept and sustainable competitive advantage so as to make decision to implement CSR in organization.